Next generation information and communcation technology for smart water utilities - Moya, C. (2020)
The process of making operational and maintenance decisions in a water network management involves the analysis of a huge number of highly interrelated variables. Current management software systems are based on data gathering and modelling technologies. Nevertheless, an increased complexity in monitoring is rarely a synonym of a better efficiency. Having taken this into account, it can be certainly suggested that new approaches and technologies are required to leverage the already existing ones. A combined work of artificial intelligence, machine learning and realtime predictive analytics forms a decisive part of the next generation of Information and Communication Technology (ICT) systems for Water Utilities.